Effects of empagliflozin on quality of life and healthcare use and costs in chronic kidney disease: a health economic analysis of the EMPA-KIDNEY trialResearch in context - Junwen Zhou; Claire Williams; Natalie Staplin; Parminder K. Judge; Kaitlin J. Mayne; Nikita Agrawal; Ryoki Arimoto; Jennifer B. Green; David Z.I. Cherney; Katherine R. Tuttle; Jose Leal; Philip Clarke; et al. (EClinicalMedicine)
Summary: Background: Sodium-glucose co-transporter 2 inhibitors (SGLT2i) slow progression of chronic kidney disease (CKD) but there is no randomised evidence of their effects on health-related quality of life (QoL) and healthcare use. We explored the effects of empagliflozin on health-related QoL, healthcare use and UK healthcare costs in the EMPA-KIDNEY trial. Methods: EMPA-KIDNEY, a randomised, double blind, placebo-controlled, phase 3 trial, was conducted at 241 centres in eight countries (Canada, China, Germany, Italy, Japan, Malaysia, the UK, and the USA), and included participants aged 18 years or older with an estimated glomerular filtration rate (eGFR) of 20 to <45 mL/min/1.73 m2, or with an eGFR of 45 to <90 mL/min/1.73 m2 and a urinary albumin-to-creatinine ratio (uACR) of ≥200 mg/g at screening. They were randomly assigned (1:1) to receive empagliflozin 10 mg once daily or matching placebo. We estimated the effect of empagliflozin (UK£1.31/day) on exploratory outcomes (unless otherwise specified) of quality-adjusted life years (QALYs), UK costs (2023 UK£) of hospital admissions (a prespecified secondary outcome), concomitant medications and end-stage kidney disease (ESKD; a prespecified tertiary outcome) management over 2 years on study treatment (median active-trial follow-up) and on ESKD costs over 2 further years off study treatment (median post-trial follow-up) using shared parameter models analysing outcomes together with time to death or negative binomial models. The trial is registered with ClinicalTrials.gov, NCT03594110. Findings: Between May 15, 2019 and April 16, 2021, 6609 participants were randomly assigned to empagliflozin (3304 participants) or matching placebo (3305 participants) in the active-trial which lasted for a median of 2.0 years. Among them, 4891 (74%) were enrolled in the post-trial follow-up. Per participant allocated to empagliflozin over 2 years, total empagliflozin cost was £826 (95% confidence interval: 818 to 835), QALYs were 0.012 higher (0.001 to 0.022), with less cost for hospital admission (−£239, −449 to −29), concomitant medications (−£130, −214 to −47), and management of ESKD (−£208, −414 to −2) compared to placebo. Over a further 2 years of post-trial follow-up off study treatment, there were additional per participant ESKD cost savings (−£842, −1441 to −242), resulting in net total healthcare cost of −£593 (−1384 to 198) over 4 years. The probability of 2 years of empagliflozin treatment being cost-effective at £20 K threshold in the UK was 43% over 2 years of follow-up and 91% over 4 years. The relative effects of empagliflozin on each cost component were similar across categories by baseline levels of eGFR, uACR and diabetes status, with larger reductions in healthcare costs estimated in categories at higher risk of CKD progression. Interpretation: In EMPA-KIDNEY, 2 years treatment with empagliflozin improved QALYs, and reduced use and cost of other healthcare, resulting in high likelihood of cost-effectiveness across a broad range of patients with CKD. The study's key limitation is its relatively short active treatment period and follow-up duration, which may lead to underestimation of the cost-effectiveness of long-term SGLT2i treatment in CKD. Funding: Boehringer Ingelheim, Germany; Eli Lilly, USA; Medical Research Council, UK; British Heart Foundation, UK; Health Data Research, UK; National Institute for Health and Care Research, UK.